Connections associated with a healthy spirituality: are these unrecognized intermediary determinants that shape health inequities in Canadian young people? - Valerie Michaelson; Nathan King; Karen A. Patte; Pauli Gardner; William Pickett (BMC, 2023)
Abstract Background The health of adolescents is determined by structural and intermediary factors. Such factors operate through pathways that foster different opportunities to achieve health and wellbeing, contributing to inequities. Past analyses of cross-national adolescent health data show that measures of child spirituality, conceptualized as the strength of the connections in our lives, may operate as intermediary determinants in some Western countries. Inspired by this idea, the current analysis provides an in-depth exploration of such pathways among Canadian adolescents. Our objectives were to confirm the existence of relationships between economic position and seven indicators of adolescent health status, then explore whether any observed inequities could be explained by the strength of connections afforded by a healthy spirituality. Methods Cycle 8 of the Canadian Health Behaviour in School-aged Children (HBSC) study was conducted in 2017-18. A school-based sample (n = 18,962) of adolescents was obtained from across Canada following a standard cross-national protocol. Eligible participants completed a general survey about their health, health behaviours and their determinants. Survey data were used to model the potential effect of perceived levels of relative affluence on each of seven health indicators. Comparison of crude and adjusted relative risks estimates from weighted log-binomial regression models provided evidence of indirect mediating effects attributable to each of four domains of spirituality. Results As perceived levels of family affluence increased, the percentages of young people who reported each (7/7) of the negative health outcomes decreased. The spiritual health domain "connections to self" (i.e., the importance of meaning, purpose, joy and happiness in life) mediated the strength of relationships between relative affluence and each (7/7) of the outcomes in boys and girls. "Connections to others" (the importance of kindness, respect and forgiveness) mediated the strength of relationships between relative affluence and each (7/7) of the outcomes among girls. Inconsistent evidence of possible mediation was identified for connections to others in boys, as well as the other two domains of spirituality (connections to nature, then connections to the transcendent) in boys and girls. Conclusion Specific connections afforded by a healthy spirituality could be intermediary determinants of health in Canadian adolescent populations.